Mesonic Stiff Fluid Distribution in Bianchi Type Space-Times - Mohanty, G.; Sahu, S. K.; Sahoo, P. K. (Communications in Physics, 2007)
The distributions of stiff perfect fluid coupled with zero mass scalar field in LRS Bianchi type-I & Bianchi type-V space times are investigated. Some physical and geometrical properties of the models are discussed.